Connective Tissue Disease Current State of the Art - Takeda, Akira (IntechOpen, 2020)
Connective tissue diseases (CTDs) comprise a number of systemic autoimmune disorders and related conditions characterized by rheumatic manifestations, production of myriad autoantibodies, and varied immune-mediated organ injury. To achieve the best outcomes for patients, accurate evaluation has become critical, and thus advanced diagnostic and assessment modalities have been developed that have had a revolutionary impact in precise characterization of the disease conditions in CTDs. This book provides an in-depth look at the current state of CTDs, while also presenting an overview that is easily understandable to newcomers to the field. Chapters cover such conditions as rheumatoid arthritis, lupus, systemic sclerosis spectrum diseases, and spondyloarthritis, as well as the importance of physical activity and exercise training in the clinical course of CTDs.